Description of Lutzomyia velezi, a new species of phlebotomine sand fly (Diptera: Psychodidae) from the Department Antioquia, Colombia (2010)
ABSTRACT: The phlebotomine sand fly Lutzomyia velezi sp.nov. was described and illustrated from male specimens collected by light trap in the Reserva Natural Cañon del Río Claro in the Central Cordillera of the Colombian Andes. The new species belongs to the series sanguinaria of the subgenus Helcocyrtomyia, which is represented in Colombia by Lutzomyia cirrita, Lutzomyia hartmanni, Lutzomyia sanguinaria, Lutzomyia scorzai, Lutzomyia sp. of Pichindé and Lutzomyia tortura. The new species can be differentiated from others of the subgenus by the combination of the following characteristics: long antennal ascoids, reaching level of the papilla, coxite with a single basal seta and fifth palpomere longer than or equal to the sum of the lengths of the third and fourth palpomeres.